PERSONAL FINANCE: A STUDY WITH STUDENTS OF SCIENCES ACCOUNTING FACULTY OF A PRIVATE INSTITUTON FROM SANTA MARIA – RS - Souto Bolzan Medeiros, Flaviani (2014)
This paper aims to investigate the behavior of students of the Undergraduate Accounting Program of a private institution of higher education in Santa Maria – RS, regarding their personal finances. Methodologically, we adopted a quantitative and descriptive research, with data obtained through a questionnaire in a sample of 178 students of the course previously mentioned. The results showed that most students surveyed have demonstrated awareness their income received, and they can handle their own personal finances. It is highlighted that generally they tend to pay for their purchases in cash.